Training systems for correction of cognitive impairments in children and adolescents after antineoplastic therapy for malignant neoplasms of the central nervous system - Alena S. Pchelintseva; Roman B. Miroshkin; Elena V. Fisun; Elena V. Zhukovskaya; Alexandr F. Karelin (Rossijskij psihologičeskij žurnal.)
Introduction. Previous research has documented the development of patients treated for malignant neoplasms (MN). Neurotoxicity of antineoplastic therapy leads to motor and cognitive impairments which affect memory and concentration. The present study attempts to test and evaluate the effectiveness of innovative methods of the correction of cognitive impairments using the Cognisens NeuroTracker training system. Materials and Methods. The study reviews (a) the methods of psychological testing of impairments, (b) the operating principle of training systems, (c) the options of training modes, and (d) clinical characteristics of the examined groups of patients. The pilot study involved 40 patients with the central nervous system (CNS) tumors at the age of 6–18 years. All the patients were treated in the Russkoe Pole (Russian Field) Rehabilitation Research Center of Dmitry Rogachev National Research Center of Pediatric Hematology, Oncology, and Immunology of the Ministry of Health of the Russian Federation in 2016. Results. The study summarized the data obtained in psychological testing, the specificity of cognitive impairments, and the test of cognitive training systems in neurorehabilitation. The results of the complex clinical psychological diagnostics assessing cognitive and motor spheres determined the original status of patients. The present study assessed the validity and effectiveness of Cognisens NeuroTracker neurocognitive training system among patients with MN. The parameters of mental manipulation of visual and spatial images, solving problems of spatial orientation of moving objects, prediction and extrapolation have improved by the end of the training period consisted of 6 sessions. The results of memory and concentration training by the Cognisens NeuroTracker confirmed their effectiveness. These trainings improved the respondents’ effectiveness and success in these types of activity. Conclusion. The Cognisens NeuroTracker new cognitive training system was successfully approved. This new direction is perspective in the rehabilitation of patients treated for MN.  Keywords: malignant neoplasms, neurotoxicity, children, cognitive disorders, psychological status, psychological testing, cognitive training systems, Cognisens NeuroTracker, rehabilitation